Developing an observational design for epibenthos and fish assemblages in the Chukchi Sea. (April 2019) - Iken, K.; Mueter, F.; Grebmeier, J.M.; Cooper, L.W.; Danielson, S.L.; Bluhm, B.A.
Abstract: In light of ongoing, and accelerating, environmental changes in the Pacific sector of the Arctic Ocean, the ability to track subsequent changes over time in various marine ecosystem components has become a major research goal. The high logistical efforts and costs associated with arctic work demand the prudent use of existing resources for the most comprehensive information gain. Here, we compare the information that can be gained for epibenthic invertebrate and for demersal fish assemblages reflecting coverage on two different spatial scales: a broader spatial coverage from the Arctic Marine Biodiversity Observing Network (AMBON, 67 stations total), and the spatial coverage from a subset of these stations (14 stations) that reflect two standard transect lines of the Distributed Biological Observatory (DBO). Multivariate cluster analysis was used to discern community similarity patterns in epibenthic invertebrate and fish communities. The 14 stations reflecting the two DBO lines captured about 57% of the epibenthic species richness that was observed through the larger-scale AMBON coverage, with a higher percentage on the more southern DBO3 than the northern DBO4 line. For demersal fishes, both DBO lines captured 88% of the richness from the larger AMBON spatial coverage. The epifaunal assemblage clustered along the south-north and the inshore-offshore axes of the overall study region. Of these, the southern DBO3 line well represented the regional (southern) epifaunal assemblage structure, while the northern DBO4 line only captured a small number of the distinct assemblage clusters. The demersal fish assemblage displayed little spatial structure with only one coastal and one offshore cluster. Again, this structure was well represented by the southern DBO3 line but less by the northern DBO4 line. We propose that extending the coverage of the DBO4 line in the northern Chukchi Sea farther inshore and offshore would result in better representation of the overall northern Chukchi epifaunal and fish assemblages. In addition, the multi-annual stability of epifaunal and, to a lesser extent also fish assemblages, suggests that these components may not need to be sampled on an annual basis and sampling every 2–3 years could still provide sufficient understanding of long-term changes. Sampling these assemblages every few years from a larger region such as covered by the AMBON project would create the larger-scale context that is important in spatial planning of long-term observing.